Plasma EphA2 level is a superior biomarker to Del-1 for sepsis diagnosis and prognosis - Lee, Eun Hye; Shin, Mi Hwa; Kwak, Se Hyun; Choi, Ji Soo; Leem, Ah Young; Lee, Su Hwan; Chung, Kyung Soo; Kim, Young Sam; Lee, Sang-Guk; Park, Moo Suk (Frontiers in Medicine, 2025)
BackgroundSepsis, characterized by a dysregulated host response to infection, often leads to organ dysfunction, and vascular endothelial dysfunction plays a central role. The erythropoietin-producing hepatocellular carcinoma (Eph)A2 receptor is associated with increased vascular permeability; however, the developmental endothelial locus-1 (Del-1), has contrasting effects on endothelial function. Hence, we examined their potential as biomarkers of sepsis.MethodsIn total, 117 participants, including 20 healthy controls, 21 patients with systemic inflammatory response syndrome (SIRS), and 76 patients with sepsis, were enrolled in this study. Sepsis severity was assessed using the Acute Physiology and Chronic Health Evaluation (APACHE) II and the Sequential Organ Failure Assessment (SOFA) scores.ResultsThe Median plasma EphA2 levels increased progressively from healthy controls to SIRS and sepsis cases (154.29, 293.52, and 554.24 pg/mL; all p < 0.05). The median plasma Del-1 levels were highest in healthy controls, lowest in SIRS, and intermediate level in sepsis (101.27, 16.88, and 36.9 pg/mL; all p < 0.001). The levels of both biomarkers were higher in 28-day non-survivors than in survivors, in patients with sepsis (EphA2:898.09 vs. 475.88 pg/mL, p < 0.001; Del-1:46.09 vs. 32.68 pg/mL, p = 0.193); however, only EphA2 was statistically significant. The area under the curve for the EphA2 was 0.74 in the receiver operating characteristic curve analysis for predicting 28-day mortality, whereas APACHE II, SOFA, and Del-1 showed values of 0.762, 0.614, and 0.595, respectively. Kaplan–Meier analysis using these cutoffs revealed that survival was significantly higher in the group with both low EphA2 and Del-1 levels compared to the group with high levels of both markers (p < 0.001).ConclusionPlasma EphA2 levels consistently increased with sepsis severity, suggesting its biomarker value for sepsis diagnosis and prognosis. In contrast, plasma Del-1 response was variable, indicating its limited prognostic utility.